Link-Blockage Model and AP-Placement Scheme for No-Blockage Link between AGV and AP in Logistics–Warehousing VLC Network - Guiyu Gong; Chaoqin Gan; Yong Fang; Yifan Zhu; Qiuyue Hu (Photonics, 2022)
In this paper, the blockage problem of the optical link between AGV (autonomous ground vehicles) and AP (access point) in the logistics–warehousing VLC (visible light communication) network is analyzed. First, based on the random geometric model, a link-blockage model is proposed. Given the position of AGV, AP and obstacle, the blockage state of the VLC link between AGV and AP can be obtained through this model. Then, an AP-placement scheme based on the link-blockage model is proposed. Under this AP placement, AGVs in any position have a reliable link that is not affected by obstacles. During the movement of AGV, the VLC link of AGV will not be interrupted by a random blockage. Finally, the effectiveness of the link-blockage model is demonstrated by the shadow method. In this paper, the link outage probability and the data rate under different AP heights, AP spacings and the number of obstacles are simulated. Simulation results show that the VLC link can keep uninterrupted under the AP placement proposed in this paper.